Address on the opening Alexander von Humboldt Season in Quito, Ecuador, on 13 February 2019 (With an introduction by Ottmar Ette) - Frank-Walter Steinmeier, Federal President (HiN - Alexander von Humboldt in the Net. International Review for Humboldt Studies, 2019)
No abstract available.